Proceedings of the 21st National Symposium on Mathematical Sciences (SKSM 21) germination of mathematical sciences education and research towards global sustainability, 6-8 November 2013, Penang - Mohd Tahir Ismail; Syakila Ahmad; Rosmanjawati Abdul Rahman (Conference collection (AIP Proceddings), 2014)
The 21st National Symposium on Mathematical Sciences (SKSM 21) was held on November 6-8, 2013 in Penang Malaysia. The aim of this symposium is to bring together mathematicians and mathematical practitioners in Malaysia to promote collaboration and sharing of knowledge on mathematical sciences, and also to create oppurtunities to highlight new discoveries and innovations of concepts that can be further developed in line with the theme of this symposium, "Germination of Mathematical Sciences Education and Research towards Global Sustainability".